Does the Formal Financial Sector Enhance Small Business Employment Generation in Nepal: Evidence from Cross-Sectional Data (Journal of Social Economics Research, 2021)
Small business enterprises are widely recognized as a driving force of economic growth and development in any nation. Empirical evidence has shown that they contribute to job creation, help to alleviate poverty, and increase a nation’s level of productivity. In the exponential increase of small businesses, the role of the financial sector is crucial. This paper aims to identify the role of formal financial support in small business employment generation in Bouddhanath, Kathmandu. The study adopted a descriptive research design. Purposive sampling was used to select 285 business owners. A structured questionnaire was designed to collect their responses. Primary and secondary data was employed to analyze user status. Data analysis was performed with the help of descriptive analysis and a financial support index. The results showed that financial support plays a critical role in the enhancement of the small business sector, allowing businesses to create employment opportunities which further helps to maintain the Nepalese economy. The major challenges to the growth of small businesses in Nepal lie in securing initial funding and overreliance on credit. In addition, the ability to afford quality staff has an equally strong effect on the success of small businesses. Business growth clearly depends on the role of the formal financial sector to achieve the desired outcomes.